The Use of ATR-FTIR Spectroscopy for Quantification of Adsorbed Compounds - Giora Rytwo; Roee Zakai; Bernd Wicklein (Journal of Spectroscopy)
Quantification of adsorbed amounts requires in most cases several assumptions. Adsorption of organic compounds, for example, is usually measured indirectly, by mass balance calculations based on the evaluation of the remaining chemical in solution. Such procedure might yield overestimates when precipitation or degradation of the adsorbate occurs and underestimates when separation of the sorbent material (e.g., clay particles) with the adsorbed chemical is not effective. This study presents a simple quantification procedure based on the ratio between IR absorption bands of the sorbate and the adsorbate. The advantages of the procedure are (a) direct evaluation of the adsorbed amount and (b) accurate measurement of chemicals that are hard to quantify, as those that do not absorb light in the UV-Visible range, or require expensive chromatography procedures.